Enabling Cocreation With Transformative Interventions: An Interdisciplinary Conceptualization of Consumer Boosting. (February 2022) - Bieler, Martin; Maas, Peter; Fischer, Lukas; Rietmann, Nele
Service research emphasizes the relevance of consumers' participation in the cocreation of transformative outcomes like health and well-being. However, in complex services, consumers' limited operant resources and lacking resource integration efficiency hinder transformative value cocreation. Service research on mechanisms that facilitate well-being through efficient resource integration is sparse, but several disciplines elaborate cognitive interventions with that target. These interventions have been validated in various contexts. Nevertheless, concerns persist that they can hurt, rather than help, individual consumers. Overcoming such limitations requires an interdisciplinary effort. The present article outlines the new research area "transformative consumer interventions" (TCI) by integrating interventions theory, consumer psychology, and transformative service research in a health context. TCI provide theory-driven principles for the selection and design of interventions that facilitate operant resource integration in complex services. Additionally, we conceptualize consumer boosting, the first TCI-based intervention construct. Consumer boosts are efficient, context-specific, and personalized interventions that enhance individuals' operant resources. Consumer boosting provides a pathway to transformative cocreation and alleviates the risk of unintended consequences and value co-destruction. This research illustrates that the transformative service domain stands to benefit substantially from getting involved in the discussion on consumer interventions and offers a unique perspective for further conceptual elaboration.